2021
DOI: 10.1098/rspb.2021.1821
|View full text |Cite
|
Sign up to set email alerts
|

Ecological specialization, rather than the island effect, explains morphological diversification in an ancient radiation of geckos

Abstract: Island colonists are often assumed to experience higher levels of phenotypic diversification than continental taxa. However, empirical evidence has uncovered exceptions to this ‘island effect’. Here, we tested this pattern using the geckos of the genus Pristurus from continental Arabia and Africa and the Socotra Archipelago. Using a recently published phylogeny and an extensive morphological dataset, we explore the differences in phenotypic evolution between Socotran and continental tax… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(18 citation statements)
references
References 73 publications
3
15
0
Order By: Relevance
“…In addition, both species present a distinctive tail ornamentation that can be used as a clear morphological diagnostic feature between them. These findings seem to be consistent with the idea that habitat diversity leads to species and morphological diversification (Losos and Parent 2009;Tejero-Cicuéndez et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…In addition, both species present a distinctive tail ornamentation that can be used as a clear morphological diagnostic feature between them. These findings seem to be consistent with the idea that habitat diversity leads to species and morphological diversification (Losos and Parent 2009;Tejero-Cicuéndez et al 2021).…”
Section: Discussionsupporting
confidence: 90%
“…We used a combination of phenotypic, phylogenetic, and ecological data to characterize and evaluate intra- and interspecific allometric trends. The data utilized here were obtained from our prior work on this system [30,31], and are briefly described here. First we used a time-dated, molecular phylogeny of squamates that included all members of the genus Pristurus, including several currently undescribed taxa.…”
Section: Methodsmentioning
confidence: 99%
“…The Afro-Arabian geckos in the genus Pristurus afford the opportunity to elucidate the inter-digitating effects of allometry and habitat specialization on clade-level patterns of phenotypic diversity. Prior work on this system [30] revealed that the colonization of ground habitats has been a trigger of morphological change, specifically reflected in an increase in body size and shape disparity. Interestingly, some ground-dwelling species are among the largest of the genus and also show increased relative head sizes and limb proportions, while some other species with this ecological specialization have evolved to be among the smallest of the group.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most likely biogeographical scenarios at all internal nodes of a given time-calibrated evolutionary tree can be estimated using maximum likelihood or Bayesian approaches, notably with the dispersal–extinction–cladogenesis (DEC) model [ 85 , 89 , 90 , 91 , 92 ]. The DEC model and its derivatives [ 93 ] allow for investigation of time-calibrated phylogenies with extant and extinct taxa while considering tectonic evolution via the incorporation of time bins in which the connectivity between any two areas can change through time [ 94 , 95 ]. Geological connectivity can be coded as a matrix of connection/disconnection relying on the latest palaeogeographical scenarios (e.g., [ 96 ]) for a given region.…”
Section: Advances In Integrated Phylogeneticsmentioning
confidence: 99%